# algebra

posted by .

-12X^6+24x^5-18x^2/-6x^2=2x^4+24x^3-3x

could some one check this for me please

• algebra -

You can check yourself by multiplying -6x^2(2x^4+24x^3-3x)

• algebra -

-12x^6+24x^5-18x^2=2x^4+4x^3+3x

## Similar Questions

1. ### Algebra (Re.: Reiny)

The fact that there was that nice symmetry to the question, makes it easier than it first appears. I had it as: (a/b + b/a)÷(b/a - a/b) look at (a/b + b/a) the common denominator for this would be ab, so a/b + b/a = (a^2 + b^2)/ab …
2. ### Algebra

checking problem Use FOIL to multiply: (6x – 1)(3x – 4) 6x*3x + 6x*(-4) + (-1)*3x + (-1)*(-4) = 6x*3x = 18x^2 6x*-4 = -24x -1*3x = -3x -1* -4 = 4 18x^2 – 24x -3x +4 = 18x^2 – 27x + 4
3. ### Math

Find the HCF of f(x) = 6x^3 + 24x^2 + 18x, g(x) = 4x^4 + 4x^3 - 24x^2
4. ### algebra

24x^4-12x^3+48x^2/-4x 24x^4-12x^3+12(-1) 24x^4-12x^3+(-12x) 2x^4-12x^3-12x check this problem for me please
5. ### algebra

-12x^6+24x^5-18x^2/-6x^2 3x^4+x^3-3x check see if I did it right.
6. ### algebra

Did I do this problem the correct way if so is there a shorter way to explain this?
7. ### algebra

Reduce answers to lowest terms. 1.) 2x/2x^2+5x-3 + 5/x^2-9 = 2.) x-3/12x^3-18x^2 - x+1/16x^2-24x = 3.) 2x/x^2-2x-15 - x-2/3x^2+9x =
8. ### alg2 check?

solve 3(8x-2)=46-2(12x+1) 24x-6=46-24x+2 24x-6=48-24x 48x-6=48 48x=42 x=42/48 or 7/8 what where the two mistakes made in the problem?
9. ### Math

consider the equations:f(x)=-6x-1 and g(x)=4x^2 Select the solution for (f+g)(x) A) -6x-1+4x^2 B) -24x^3 - 4X^2 C) -24x^2 - 1 D) -6X -1 - 24X^2 I think the answer is A. Please help
10. ### Math

(2x-1)(3x-7)(4x+3) =6x^2-14x-33x+7 =(6x^2-19x+7)(4x+3) =24x^3+18x^2-126x+28x+21 =24x^3+18x^2-88x+21 <-- my answer but the correct answer is 24x^3-50x^2-23x+21 please correct me?

More Similar Questions